2014
DOI: 10.1021/ef5005539
|View full text |Cite
|
Sign up to set email alerts
|

Self-Assembly Synthesis of Microencapsulated n-Eicosane Phase-Change Materials with Crystalline-Phase-Controllable Calcium Carbonate Shell

Abstract: Novel microencapsulated phase-change materials based on an n-eicosane core and calcium carbonate (CaCO3) wall have been synthesized through a self-assembly method. The resultant microcapsules presented rhombohedral and spherical morphologies when the synthesis was performed at different concentrations of surfactant. These two types of the n-eicosane microcapsules also exhibited a well-defined core–shell structure. X-ray diffraction patterns and Fourier transform infrared spectra confirmed that the rhombohedral… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
53
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 94 publications
(59 citation statements)
references
References 47 publications
5
53
1
Order By: Relevance
“…The dark inorganic shell could be distinctively distinguished from the light core material, and hereby, the shell thickness could be determined to be 90 nm and 200 nm when the microcapsules were synthesized with the n-eicosane/TBT weight ratio of 60/40 and 40/60, respectively. On the basis of the morphological investigation, the microcapsules developed by this work have a much larger size and more perfect outline compared to those with the amorphous TiO 2 shell reported by Cao et al [27] Additionally, the resultant microcapsules also present a more regular spherical morphology and narrower size distribution than the PCMs-based microcapsules with SiO 2 and CaCO 3 shells we reported previously [23,25,26]. These results indicate that the morphology and core-shell structure can be controlled more easily in the nonaqueous emulsion system than in the common O/W emulsion for the synthesis of the PCMs-based microcapsules with an inorganic shell.…”
Section: Morphology and Microstructuresupporting
confidence: 56%
See 1 more Smart Citation
“…The dark inorganic shell could be distinctively distinguished from the light core material, and hereby, the shell thickness could be determined to be 90 nm and 200 nm when the microcapsules were synthesized with the n-eicosane/TBT weight ratio of 60/40 and 40/60, respectively. On the basis of the morphological investigation, the microcapsules developed by this work have a much larger size and more perfect outline compared to those with the amorphous TiO 2 shell reported by Cao et al [27] Additionally, the resultant microcapsules also present a more regular spherical morphology and narrower size distribution than the PCMs-based microcapsules with SiO 2 and CaCO 3 shells we reported previously [23,25,26]. These results indicate that the morphology and core-shell structure can be controlled more easily in the nonaqueous emulsion system than in the common O/W emulsion for the synthesis of the PCMs-based microcapsules with an inorganic shell.…”
Section: Morphology and Microstructuresupporting
confidence: 56%
“…We also reported the synthesis of silica-microencapsulated PCMs using sodium silicate as a low-cost silica precursor and found that these microcapsules exhibited a well-defined core-shell structure and a uniform particle size under the moderately acidic condition [23]. The latest literature survey indicated that aluminum hydroxide, calcium carbonate, and titanium dioxide (TiO 2 ) could also be employed as inorganic wall materials for the encapsulation of PCMs [24][25][26][27]. Nevertheless, the aforementioned inorganic encapsulation technologies toward PCMs are unexceptionally developed to serve the solo function of latent heat storage.…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, the phase change temperature of the microcapsules could be adjusted from 25°C to 50°C by changing the weight ratio of binary cores. It is noteworthy that P2 exhibited obvious bimodal crystallization and melting peaks in thermograms, which attributed to the crystallization of the a-crystals and b-crystals of paraffin, respectively [38]. The phenomenon is in agreement with SEM results, the bowl-like microcapsules are precisely owing to heterogeneous and homogeneous nucleation.…”
Section: Phase Change Performancesupporting
confidence: 85%
“…Cao et al [27] investigated the encapsulation of palmitic acid with titanium dioxide in the sol-gel process, and the resulting microcapsules revealed the good phase-change potential as a shape-stabilized thermal energy-storage material. We also reported the synthesis of the microencapsulated PCMs with a calcium carbonate shell through the self-assembly method and found that these new microcapsules had a high thermal conductivity and long serving durability [28,29]. Nevertheless, the aforementioned inorganic encapsulation technologies toward PCMs were unexceptionally developed to serve the latent-heat storage as a single function.…”
Section: Introductionmentioning
confidence: 99%